ANALISIS PENGARUH KARAKTERISTIK INDIVIDU, KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (Survei Pada Karyawan PT Pos Indonesia Kantor Cabang Sukoharjo) - Novariani Indri Utami, Alwi Suddin & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this research was: 1) to analyze the significance of the influence of individual characteristics, organizational commitment, organizational culture, and job satisfaction against Organization Citizenship Behavior in employees of PT Pos Indonesia Branches Sukoharjo. 2) to analyze the dominant influence variables (characteristics of individual, organizational commitment, organizational culture, or job satisfaction) of Organization Citizenship Behavior in employees of PT Pos Indonesia Branches Sukoharjo. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of secondary. The population in this study are permanent employees of PT Pos Indonesia Branches Sukoharjo totaling 144 people. In this research technique sampling using the technique of proportional random sampling. As for the number of samples used in the study was as many as 72 people respondents. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of Linear regression analysis, classic Double, t test, F test, the coefficient of determination and the absolute difference test. The research results obtained conclusions: there is a significant influence on the characteristics of individual, organizational culture, organizational commitment, job satisfaction and Organizational Citizenship Behavior against on the employees of PT Pos Indonesia Branches Sukoharjo. Organizational culture is the dominant variables that affect Organizational Citizenship Behavior in employees of PT Pos Indonesia Branches Sukoharjo.Keywords: characteristics of individual, organizational culture, organizational commitment, job satisfaction, organizational citizenship behavior